Er–Pr doped tellurite glass nanocomposites for white light emitting diodes - Kityk, Ivan V; Nasser Saleh, Alzayed; Ahmed M., El-Naggar; Reben, Manuela; Wasylak, Jan; Lakshminarayana, Gandham; Ali Hussain, Reshak, Prof. Dr. (Elsevier B.V., 2013)
Link to publisher's homepage at http://www.elsevier.com/